The Contract Education as a Goal-oriented System of Activity - Valery M. Anikin; Boris N. Poizner; Eduard A. Sosnin (Moscow Polytechnic University, 2019)
The aim of the work is an application of the theory of Goal-oriented System of Activity to analysis and organization of effective contract targeted training at higher education institutions. The organization of targeted training of specialists is considered as one of the components of public administration to address staff problems in various regions and sectors of the economy in the context of rapidly changing demands of society, to implement promising youth policy and mitigate demographic problems. An algorithmic chain of meaningful actions is con structed on the basis of the methodology of the Goal-oriented System of Activity, which takes into account the real state of human, intellectual, material and economic resources and enables to minimize existing contradictions and, accordingly, ensure the establishment of partnerships between all interested participants in the process of targeted training (government agencies, employers, higher education institutions and students). As an example, four stages of contract teacher training have been considered.